2005
DOI: 10.1128/jvi.79.17.11214-11224.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Subtype B Ancestral Envelope Protein Is Functional and Elicits Neutralizing Antibodies in Rabbits Similar to Those Elicited by a Circulating Subtype B Envelope

Abstract: Human immunodeficiency virus type 1 (HIV-1) is a difficult target for vaccine development, in part because of its ever-expanding genetic diversity and attendant capacity to escape immunologic recognition. Vaccine efficacy might be improved by maximizing immunogen antigenic similarity to viruses likely to be encountered by vaccinees. To this end, we designed a prototype HIV-1 envelope vaccine using a deduced ancestral state for the env gene. The ancestral state reconstruction method was shown to be >95% accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 62 publications
3
94
0
Order By: Relevance
“…Although the fragment MRCAs will correspond to different nodes of the genealogy, their sequences could be used for a better depiction of the history of changes in the sample or to reconstruct specific protein domains. For example, in the case of HIV-1, the latter applies to the design of polyvalent vaccines, in which the interest is on particular epitopes spread across the entire sequence (Gao et al 2003;Nickle et al 2003;Doria-Rose et al 2005). Still, a more robust method for the reconstruction of the ancestral (GMRCA) sequence in presence of recombination is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fragment MRCAs will correspond to different nodes of the genealogy, their sequences could be used for a better depiction of the history of changes in the sample or to reconstruct specific protein domains. For example, in the case of HIV-1, the latter applies to the design of polyvalent vaccines, in which the interest is on particular epitopes spread across the entire sequence (Gao et al 2003;Nickle et al 2003;Doria-Rose et al 2005). Still, a more robust method for the reconstruction of the ancestral (GMRCA) sequence in presence of recombination is clearly needed.…”
Section: Discussionmentioning
confidence: 99%
“…The first data set was downloaded from the HIV Sequence Database (http:/ /www.hiv.lanl.gov) and included the HIV-1 group M reference alignment plus an outgroup (40 sequences, 2514 bp). The second data set included only subtype B viruses and an outgroup (38 sequences, 2557 bp) (Doria-Rose et al 2005). Sequence U19647 was too short, and therefore we removed it from the latter data set.…”
Section: Simulation Of Recombinant Sequencesmentioning
confidence: 99%
“…Initial studies have shown that these immunogens are functional, immunogenic and generate a neutralizing antibody response; however, the limited breadth of neutralization has been disappointing [187,188]. Notably, a second generation consensus Env immunogen has shown greater potential for broadly neutralizing subtype B and C primary isolates [92], but nonetheless still needs improvement.…”
Section: Novel Immunogen Design Strategiesmentioning
confidence: 99%
“…Thus, efforts to design vaccines that rapidly elicit an effective and broadly cross-reactive neutralizing Ab (nAb) response seem rational based primarily on the observation that doses of bNmAbs are the only formula to date that has been shown to prevent infection and to provide sterilizing immunity in NHP. Despite multiple efforts to develop an immunogen or immunogens that can elicit bNAbs following vaccination, success has been limited (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Some incremental advances have been made, including our recent immunogenicity studies (22) and those of others (23)(24)(25) that have shown an advantage of coimmunization with DNA and protein immunogens, including the potential of contracting the vaccine regimen to a small number of immunizations to reach peak NAb responses.…”
mentioning
confidence: 99%